Research priorities in sarcomeric cardiomyopathies - van der Velden, Jolanda (Cardiovasc Res, 2015)
The clinical variability in patients with sarcomeric cardiomyopathies is striking: a mutation causes cardiomyopathy in one individual, while the identical mutation is harmless in a family member. Moreover, the clinical phenotype varies ranging from asymmetric hypertrophy to severe dilatation of the heart. Identification of a single phenotype-associated disease mechanism would facilitate the design of targeted treatments for patient groups with different clinical phenotypes. However, evidence from both the clinic and basic knowledge of functional and structural properties of the sarcomere argues against a ‘one size fits all’ therapy for treatment of one clinical phenotype. Meticulous clinical and basic studies are needed to unravel the initial and progressive changes initiated by sarcomere mutations to better understand why mutations in the same gene can lead to such opposing phenotypes. Ultimately, we need to design an ‘integrative physiology’ approach to fully realize patient/gene-tailored therapy. Expertise within different research fields (cardiology, genetics, cellular biology, physiology, and pharmacology) must be joined to link longitudinal clinical studies with mechanistic insights obtained from molecular and functional studies in novel cardiac muscle systems. New animal models, which reflect both initial and more advanced stages of sarcomeric cardiomyopathy, will also aid in achieving these goals. Here, we discuss current priorities in clinical and preclinical investigation aimed at increasing our understanding of pathophysiological mechanisms leading from mutation to disease. Such information will provide the basis to improve risk stratification and to develop therapies to prevent/rescue cardiac dysfunction and remodelling caused by sarcomere mutations.